Peluang dan tantangan Pembelajaran Daring pada sekolah Madrasah Ibtidaiyah Swasta Madrisatul Ibrar - Wisnu Ahmad Wardana; Muhammad Gembira; Pitri Ristia Ningsih; Sri Andriani (Edumaspul: Jurnal Pendidikan, 2022)
During the COVID-19 pandemic, all activities were hampered, one of which was in the field of education. Where in every educational institution requires online or virtual learning based on regulations set by the government to break the ropes of the spread of the COVID-19 virus. However, online learning currently has both advantages and disadvantages in the online or virtual teaching and learning process. and in this study it will be discussed about the online learning process in an educational institution to see whether the obstacles and changes contained in schools in the current online learning system